Perspektif Mahasiswa Universitas Pendidikan Indonesia Terhadap Fenomena Trinkets dan Kaitannya dengan Sifat Israf - Alia Noer Khalifa; Anisa Oktafiani Futri; Haura Naya Shakira; Sabrina Azura Nariswari; Achmad Faqihuddin (Yayasan Al-Afif, 2025)
This study explores the perspectives of students at Universitas Pendidikan Indonesia regarding the trinkets trend and its association with israf (extravagance) in Islamic ethics. Using a qualitative phenomenological approach, data were gathered through open-ended surveys with 40 active students. The findings reveal that trinkets are primarily purchased for aesthetic value and self-expression, often influenced by social media and peer groups. However, repetitive and impulsive buying behaviors raise concerns over consumptive tendencies and the dilution of financial ethics. The study highlights the blurred line between needs and wants, where symbolic consumption may evolve into wastefulness if not managed. These insights urge students to adopt mindful consumerism aligned with religious values, providing a foundation for educational praxis that emphasizes ethical consumption.